If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -3 = x + 3 Reorder the terms: -3 + 3x = x + 3 Reorder the terms: -3 + 3x = 3 + x Solving -3 + 3x = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 3x + -1x = 3 + x + -1x Combine like terms: 3x + -1x = 2x -3 + 2x = 3 + x + -1x Combine like terms: x + -1x = 0 -3 + 2x = 3 + 0 -3 + 2x = 3 Add '3' to each side of the equation. -3 + 3 + 2x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 3 + 3 2x = 3 + 3 Combine like terms: 3 + 3 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 48=12h | | 3x=3x-3 | | (6x^2)+10x= | | 23n=115 | | -16x^2+96x-576=0 | | c^3d^2(c^2d-2d)=0 | | 2x^5-12x^3=-16x | | 4a^2+10a=12 | | x^2+6x-91= | | 2-4y=30+3y | | d-125=75 | | (6s^2)(2s^2)-(3s^4)(4s^3)=0 | | 50-y=30 | | w+349=761 | | 64s^2+144s+81= | | 86+m=107 | | 2=m-3+c | | 71=b-29 | | 18=-2+w | | 60=n+30 | | 2(x-2)=7x-19 | | 12s^4-12s^7=0 | | s=180-360 | | p-11=12 | | 8[3m-2]-7m=0 | | 7=-9+22 | | 19+t=51 | | n(3+n)=n^2+4n | | x-8=-9 | | -11b+4=15 | | 5=x-20 | | n(2n-3)=2 |